Analisis Forecast Kebutuhan Tempat Tidur Berdasarkan Indikator Barber Johnson di RSUD Sidoarjo - Thesalonic Kristianto; Hartaty Sarma Sangkot (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
Inpatient analysis data has been calculated using the Barber Johnson indicator at Sidoarjo Regional Hospital. The purpose of this study is to perform a forecast analysis of the need for beds based on barber Johnson calculation indicators at Sidoarjo Hospital. This type of research is descriptive quantitative research with observation methods and retrospective approaches. The population in this study is all data since Sidoarjo Hospital was founded in 1956. The sample used data analysis of hospitalization for the last 3 years, namely 2020-2022. The data collection technique uses a purposive sampling technique. This research is described in trend analysis. The results showed the ideal percentage of BOR (71.7%), ideal TOI (1 day), ideal AvLOS (4 days) and BTO not ideal (71 times). Barber Johnson's chart is outside the efficient zone. There is no need for an additional bed in 2023 and 2024, but in 2025 an additional 2 beds will be required, in 2026 an additional 12 beds will be required, and in 2027 an additional 22 beds will be required. In conclusion, Sidoarjo Hospital needs additional beds in 2025-2027 so that the Tulip room can have an optimal level of efficient use of bed.